2020
DOI: 10.1002/lol2.10164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lake warming on the seasonal risk of toxic cyanobacteria exposure

Abstract: Large spatial studies have shown that human activities are leading to a global increase in the incidence of harmful cyanobacterial blooms. However, it is unclear how concentrations of a common cyanobacterial toxin (i.e., microcystin) are changing on an interannual and seasonal basis. This study provides evidence that while temporal patterns are site-specific within a large prairie lake region, warmer temperatures result in elevated microcystin concentrations, prolonged duration of elevated toxins levels, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…Many of these species produce toxins and were dominant. Besides excessive nutrients, warming is considered a key driver of increased probability of harmful algal blooms and elevated concentrations of microcystin [62,63]. Gkelis et al [64] found that microcystin concentration correlated positively with temperature in a shallow eutrophic lake of Greece.…”
Section: Implications For Limnological Processesmentioning
confidence: 99%
“…Many of these species produce toxins and were dominant. Besides excessive nutrients, warming is considered a key driver of increased probability of harmful algal blooms and elevated concentrations of microcystin [62,63]. Gkelis et al [64] found that microcystin concentration correlated positively with temperature in a shallow eutrophic lake of Greece.…”
Section: Implications For Limnological Processesmentioning
confidence: 99%
“…For most but not all lakes, climate change is recorded as warmer water temperatures (O'Reilly et al 2015). Higher temperatures are linked to increasing algal blooms in general (Ho et al 2019), as well as harmful algal blooms that create toxic water conditions (Hayes et al 2020). Reductions in ice cover have been widely documented, which can affect many aspects of lake ecosystems.…”
Section: Masumi Stadlermentioning
confidence: 99%
“…Moreover, cyanobacteria could release Microcystin, which could threaten the safety of the drinking water and the health of animals on land and of human beings [6]. The Microcystin concentration in waters has been a critical indicator for evaluating the quality of drinking water by the World Health Organization (WHO), the Environmental Protection Agency (EPA) in the United States, and the EU Water Framework Directive [7].…”
Section: Introductionmentioning
confidence: 99%